New Genus and Species of Empheriidae (Insecta: Psocodea: Trogiomorpha) and Their Implication for the Phylogeny of Infraorder Atropetae - Li, Sheng; Yoshizawa, Kazunori; Wang, Qiuzhu; Ren, Dong; Bai, Ming; Yao, Yunzhi (Frontiers in Ecology and Evolution, 2022)
Two species of psocids discovered from Mid-Cretaceous Burmese amber, Latempheria kachinensis Li, Yoshizawa & Yao, gen. et sp. nov. and Burmempheria curvatavena Li, Yoshizawa & Yao, sp. nov., are described and assigned to the family Empheriidae (Trogiomorpha: Atropetae). A phylogenetic analysis of the infraorder Atropetae is conducted based on 38 morphological characters of three outgroups and fifteen ingroups, which supported the monophyly of Atropetae including fossil and extant taxa. In the phylogenetic result, all the genera of fossil families Empheriidae and Archaeatropidae form a monophyletic group, sister to the extant members of Atropetae. But each fossil family as a single is recovered paraphyletic. The two fossil families also share a lot of similarities in morphology, locality and geological period. Recently discovered fossil species exhibited combined morphological characters of both families. Based on these observations and on the results of the phylogenetic analyses, Archaeatropidae is here treated as new junior synonym of Empheriidae.